Impact of coronavirus (COVID-19) pandemic on physical activity levels in different sub-populations of Iranians: a national survey - Hamid Arazi; Behzad Taati (Scientific Reports)
Abstract During the COVID-19 pandemic, the level of physical activity (PA) has been reported to decrease worldwide. A sedentary lifestyle is widely recognized as a significant risk factor for various diseases, necessitating extensive big data analysis to uncover the diverse aspects linked to the COVID-19 pandemic. Therefore, the aim of this study was to investigate the impact of the COVID-19 pandemic on PA levels across diverse population subsets in Iran and to identify the barriers to PA during the fifth wave of COVID-19 outbreak. Data from 7810 individuals (50.8% male, 54.8% married, 69.6% 18–49 years) were collected using a standardized questionnaire comprising demographic details, levels of high, moderate, and low PA, daily sedentary time, PA at home, and barriers to PA. The questionnaire was distributed online via social platforms such as Telegram, WhatsApp, and Instagram. The obtained data were analyzed using the Chi-Square goodness-of-fit test and the Chi-Square test at a significance level of α < 0.05. During the COVID-19 pandemic, there was a significant decrease in the number of days/week dedicated to high, moderate, and low PA, as well as a reduction in the duration of each PA session compared to pre-pandemic levels (p < 0.001). Conversely, the duration of daily sedentary time, particularly exceeding 5 h, significantly increased post-outbreak (p < 0.001). Notably, lack of appropriate space and time constraints were identified as the primary barriers to PA during the COVID-19 pandemic (p < 0.001). In this nationally representative study, the findings underscore a substantial decline in PA levels across diverse sub-populations in Iran and an increase in sedentary behaviors during the COVID-19 crisis.